Nucleus‐Targeting Carbon Quantum Dots Assembled with Gambogic Acid via π–π Stacking for Cancer Therapy Cancer (Adv. Therap. 1/2023). Issue 1 (18th January 2023) - Liu, Shanshan; Wang, Jianfeng; Li, Haiguang; Xu, Chen; Guo, Yimin; Bao, Xiaotong; Guan, Shaokang; Liu, Hairong; Zhang, Tao
Abstract : Carbon quantum dots assembled with gambogic acid via a π–π stacking interaction for cancer therapy have a high drug loading and targeted drug delivery, which can overcome drug resistance, short circulation, and retention in cells, thereby exhibiting a significant inhibitory effect on the growth of HepG2 and HeLa cells. This is reported by Jianfeng Wang and co‐workers in article number 2200201 .